2007
DOI: 10.1016/j.jfe.2007.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Economic lessons from control efforts for an invasive species: Miconia calvescens in Hawaii

Abstract: Once established, invasive species can rapidly and irreversibly alter ecosystems and degrade the value of ecosystem services. Optimal control of an unwanted species solves for a trajectory of removals that minimizes the present value of removal costs and residual damages from the remaining population. The shrubby tree, Miconia calvescens, is used to illustrate dynamic policy options for a forest invader. Potential damages to Hawaii's forest ecosystems are related to decreased aquifer recharge, biodiversity, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 8 publications
1
36
0
Order By: Relevance
“…These future expected costs are based on the population that is left remaining after current intervention activities are undertaken and its ability to reproduce and spread, and the damages from those future ecological changes, and the future costs of intervening to manage them. (See, for example, Burnett et al, 2007). In addition, policy expenditures across intervention options should also equate marginal benefits and costs.…”
Section: Valuation Of What Is "At Stake"mentioning
confidence: 99%
“…These future expected costs are based on the population that is left remaining after current intervention activities are undertaken and its ability to reproduce and spread, and the damages from those future ecological changes, and the future costs of intervening to manage them. (See, for example, Burnett et al, 2007). In addition, policy expenditures across intervention options should also equate marginal benefits and costs.…”
Section: Valuation Of What Is "At Stake"mentioning
confidence: 99%
“…First, a greater amount of invasion edge decreases the range of control costs for which containment is optimal, shifting policies 11 Several other studies have found that delaying control can be optimal, but for different reasons than shape. Burnett et al (2007) and Olson and Roy (2008) find that when control costs are stock dependent (i.e., higher marginal control costs for smaller invasions), delaying control to reduce control costs can be optimal. For example, Burnett et al suggest that delaying control is optimal for Miconia invasions on some of the Hawaiian islands.…”
Section: Invasion Shape and Contiguitymentioning
confidence: 99%
“…While there has been substantial research published on invasive species management (Epanchin-Niell and Hastings 2010), important gaps remain, particularly concerning general management strategies. Many recommendations are problem-specific and do not give general insights that could support rapid decision-making for new problems, even when these new problems are similar to those already treated in the existing literature (Higgins et al 2000, Burnett et al 2007, Hyder et al 2008.…”
Section: Introductionmentioning
confidence: 99%